Electronic Banking: A Sustainable Tool for Customer Satisfaction in the Nigerian Banking Sector - Imouokhome, Ebun O.; Akenzua, Princess Oghogho Uyi (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025, 2025)
Electronic banking has grown remarkably in Nigeria because customers view it as a way out of poor-quality services rendered on the counter which is labelled with the system of banking in Nigeria. The study seeks to assess the impact of electronic banking on customer satisfaction in the Nigerian banking sector while the precise objectives include; (i) determining the impact of mobile banking app on customer satisfaction of users of GT Bank within Ilorin Metropolis, and (ii) assess the influence of Web banking on customer satisfaction of users of GT Bank within Ilorin Metropolis. The descriptive survey design was adopted by the study, and a sample size of 397 was arrived at using the Taro Yamane technique for sample size determinant for an infinite population. The method employed for data analysis is linear regression analysis. The study outcome reveals that mobile and web banking significantly affect customer satisfaction. The study, concludes that electronic banking is significant on customer satisfaction, on of GT bank. The bank’s engagement in electronic banking tends to incur an increase or change in customer satisfaction. The study recommends that GTB should constantly ensure a very friendly App that will be easy to understand for their subscribers and a very secure web to ensure that customers’ transactions are save. Keywords: Banking App, Customer Satisfaction, Electronic-banking, Mobile banking, Web banking.